2008
DOI: 10.1111/j.1467-8551.2007.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transformational Leadership on Organizational Performance through Knowledge and Innovation*

Abstract: Today's information and knowledge society requires new leaders who can confront a reality based on knowledge and foster innovation to achieve improvements in organizational performance. However, organizations sometimes fail to achieve sustainable competitive advantage due to their limited understanding of the relationships between these strategic variables. To date, very little research has analysed the direct and indirect relationships between these variables. Our study seeks to fill this research gap by anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
251
1
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(276 citation statements)
references
References 85 publications
(198 reference statements)
9
251
1
15
Order By: Relevance
“…TMT BI and SDC were shown to increase adaptability, which is crucial for the viability of small entrepreneurial firms. In so doing, we extend research that seeks to unravel TMT attributes and processes shaped and facilitated by transformational leaders in their pursuit of innovative, entrepreneurial and effective organizations (Garcia-Morales et al, 2008;Ling et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TMT BI and SDC were shown to increase adaptability, which is crucial for the viability of small entrepreneurial firms. In so doing, we extend research that seeks to unravel TMT attributes and processes shaped and facilitated by transformational leaders in their pursuit of innovative, entrepreneurial and effective organizations (Garcia-Morales et al, 2008;Ling et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, positive TMT dynamics and supporting processes need to be in place so that both the availability of information and the willingness to share and analyse it will allow for strategic capacities to emerge and develop. We posit that transformational leadership creates a work environment in which followers are motivated to cooperate with others (Shamir et al, 1993), a common mentality is shaped (Garcia-Morales et al, 2008), and communication networks for transfer of knowledge are strengthened (Senge, 1990;Slater and Naver, 1995). Specifically, CEO transformational leadership is exercised through TMT BI as an enabling mechanism and through SDC as a strategic decision process.…”
Section: The Mediating Role Of Tmt Behavioural Integration and Stratementioning
confidence: 99%
See 1 more Smart Citation
“…С трансформа-ционным лидерством связана эффектив-ность командной работы [Judge, Bono, 2000;Dionne et al, 2004]. Трансформационное лидерство усиливает «поглощающую спо-собность» (absorptive capacity), рыночную ориентацию и готовность к обучению, не-обходимые для осуществления инноваций и организационных изменений [Garcia-Morales, Llorens-Montes, Verdu-Jover, 2008;Kraft, Bausch, 2016]. Оно оказывается по-зитивно связанным и с социальной эффек-тивностью бизнеса, повышая общее каче-ство трудовой жизни работника [Arnold et al, 2007], оценку работниками своего ру-ководителя как этичного [Bass, Steidlmeier, 1999;Brandt, Laiho, 2013].…”
Section: трансформационное лидерство: концепция и эмпирические исследunclassified
“…Not only this, such leadership also acts to guide and motivate members of said organization towards their common goal, hence a clear vision must be established. [9] By motivating workers to create and share knowledge, along with the implementation of innovative learning, these leaders are building and strengthening their company's leadership foundations [10]. Scott and Bruce (1994) found that leader's behavior did indeed predict climate for innovation within organizations through the Leader Member Exchange Theory (LMX).…”
Section: The Leadership Needmentioning
confidence: 99%